HUBUNGAN POLA ASUH DENGAN MASALAH PERILAKU DAN EMOSI PADA SISWA SD DI KECAMATAN PENJARINGAN JAKARTA UTARA - Anindita Agung Pradnya Savitri; Surilena Surilena; Erfen Gustiawan (Atma Jaya Catholic University of Indonesia, 2022)
Background: Parenting is defined as an act of giving education, guidance, patronage, and supervision by the parents to their children. Different methods of parenting may result in distinctive character developments as well as determining the children's behaviour and emotional demeanour. Objective: To determine the relationship between parenting towards behavioral and emotional problems among primary school student in Penjaringan, North Jakarta. Methods: This study was a cross-sectional study of 512 primary school students in Penjaringan, North Jakarta. Measuring instruments used were Strength and Difficulties Questionnaire (SDQ) dan Parenting Questionnaire Children’s Point of View. Both instruments were filled directly by students. Data analysis was performed descriptively and bivariate (chi-square). Result: There were 32% respondents with behavioral and emotional problems, among them 38.5% conduct problems; 34.2% peer problems; 25% emotional symptoms. This study finds that 66.2% respondents with Exposure parenting, among them 51.8% with type B parenting (authoritarian), 7.6% with type D parenting (Inconsistent), and 6.8% type C parenting (Permissive). Bivariate analysis found that there is significant relationship between parenting towards behavioral and emotional problems (p<0.05; 95%CI = 0.448 – 0.970; OR = 0.659). Conclusion: There is association between parenting towards behavioral and emotional problems among primary school students. Keywords: Parenting, behavioral and emotional disorder, children, elementary school